Optimalisasi Pencegahan Ansietas Ibu Hamil sebelum Persalinan dengan Qigong Exercise - Puspasari, Jehan; Rahmawati, Veronica Yeni; Fitria, Dian; Juliani, Enni (Jurnal Pengabdian Kesehatan, 2025)
Pregnancy is a natural and normal process in women's life cycle which causes physiological and psychological changes. Pregnancy is very vulnerable to various health problems. Among these various problems, the most common is mental health, where the highest prevalence is anxiety disorders. The aim of this community service activity is to increase the knowledge of pregnant women in reducing anxiety facing childbirth. The method used is providing education in the form of materials and techniques to reduce anxiety with qigong exercises to pregnant women and health cadres. The results of the activity showed an increase in participants' knowledge. In the material regarding physiological changes in pregnancy, participants who had good knowledge during the pre-test were 36.6% and 93% at the post-test. In material regarding physical health problems in pregnant women, participants who had good knowledge at the pre-test were 56% and at the post-test were 97.5%. In material regarding psychological health problems in pregnant women, participants who had good knowledge at the pre-test were 51% and at the post-test were 97.5%. It can be concluded that community service activities in preventing anxiety of pregnant women before giving birth with qigong exercises have proven to increase participants' knowledge.